The influence of online information on consumers’ channel migration behavior of fresh agricultural products - Cui, Ningbo; Dong, Jin; Fan, Xiaofan; Zhao, Duanyang; Liang, Mingshuo; Shi, Jiaoyu (Frontiers in Sustainable Food Systems, 2024)
Compliance with the latest patterns in online consumption of fresh agricultural products should prioritize the shifts in consumer behavior. It is highly meaningful to clarify the influencing factors of consumers' channel migration behavior of fresh agricultural products, for further improving the online consumption stickiness, tapping the potential of online consumption and improving the circulation efficiency of fresh agricultural products in the post-pandemic era. Based on SOR theory, and from the dual perspectives of information transmission and information reception, this study exploratively introduced the network affinity of consumers, and constructed the concept model of the influencing factors of consumers' channel migration behavior of fresh agricultural products including information acquisition and risk perception. 416 valid questionnaires were used to conduct structural equation model analysis. The results indicate three conclusions. (1) Productinformation and platform information significantly affect consumers' channel migration behavior of fresh agricultural products. Product information including feature information and price information has a positive influence on consumers' channel migration behavior of fresh agricultural products. The same is true for such behavior and the platform information including service information and logistics information. (2) Risk perception plays a partial mediating role in the influence of product information variables and platform information variables on consumers' online purchasing and migration behavior of fresh agricultural products. (3) Network affinity negatively moderates the causal relationship between product information and risk perception as well as that between platform information and risk perception. The effect is more pronounced for consumers with high network affinity than those with low network affinity. These research findings provide a theoretical basis for predicting channel migration behavior of fresh agricultural products from the perspective of consumers, and can also offer practical suggestions for improving the online channel design, optimizing user experience, and promoting the sustainable development of online marketing for the e-commerce of fresh agricultural products.